1985
DOI: 10.1182/blood.v65.5.1071.1071
|View full text |Cite
|
Sign up to set email alerts
|

A unique pattern of central nervous system leukemia in acute myelomonocytic leukemia associated with inv(16)(p13q22)

Abstract: Twenty-six patients with inv(16)(p13q22) or del(16)(q22) in association with acute myelomonocytic leukemia (AMML-M4, FAB classification), and abnormal marrow eosinophils have been treated at this institute. Initial bone marrow eosinophilia (greater than or equal to 4%) was observed in 22 of 26 patients (85%), and abnormal eosinophil morphology, characterized by immature cells with some interspersed basophilic granules, was evident in 26 of 26 (100%). Giemsa-banded chromosome analysis performed in all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
3
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(33 citation statements)
references
References 28 publications
3
25
3
2
Order By: Relevance
“…Arthur and Bloomfield (1983) and subsequently Le Beau et al (1983) observed that this group of patients appeared to have an improved survival compared with ANLL patients as a whole. This finding has been supported by data from other groups (Holmes et al, 1985;Larson et al, 1986) 0 1991 WILEY-LISS, INC.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Arthur and Bloomfield (1983) and subsequently Le Beau et al (1983) observed that this group of patients appeared to have an improved survival compared with ANLL patients as a whole. This finding has been supported by data from other groups (Holmes et al, 1985;Larson et al, 1986) 0 1991 WILEY-LISS, INC.…”
Section: Introductionsupporting
confidence: 75%
“…CNS involvement is an uncommon complication of ANLL, reported in only 7-1 1% of cases (Stewart et al, 1981). However, it has been reported in the M4Eo subgroup at relapse in up to 35% of cases (Holmes et al, 1985) characteristically with mass lesions demonstrable on CT scanning (Glass et al, 1987). T h e incidence of 8% in our series is comparable with that of ANLL in general.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Today extramedullary relapse terminates remission in 5-10% of patients [1][2][3][4]. Factors predisposing to IEMR include t(8;21), inv (16) and t(11q23) and FAB M4 and M5 morphologies [6][7][8][9][10]. In this study, the blasts of 7 of 13 patients had one of these cytogenetic abnormalities and morphology was FAB M4 or M5 in 11 of 16.…”
Section: Discussionmentioning
confidence: 54%